Towards a CFD model of bubble columns containing significant surfactant levels. (4th May 2015) - McClure, Dale D.; Norris, Hannah; Kavanagh, John M.; Fletcher, David F.; Barton, Geoffrey W.
Abstract: In this work we have quantified the effect of surfactant addition on the overall hold-up, local hold-up, liquid velocity, gas velocity, bubble size distribution (BSD) and mixing time using a bubble column 0.39 m in diameter and 2 m in height operated at superficial velocities between 0.01 and 0.28 m/s. The surfactant used was 2-propanol, which was chosen because its addition causes an air/water system to behave similarly to the complex and poorly defined fermentation media used in industrial bioprocesses. The second portion of the study examines the extension of an existing computational fluid dynamics (CFD) model to account for the impact of surfactant addition; it was found that the inclusion of a correction term into the drag coefficient calculation led to predictions that were in good agreement with experimental results. Highlights: Impact of surfactant addition on pilot-scale bubble column was quantified. Measurements of mixing, BSD, hold-up, liquid and gas velocity made. CFD model of surfactant containing systems developed. Model in good agreement with experimental data.